ACTIVATION OF INDEPENDENT STUDENT STUDY ON THE BASIS OF MODERN APPROACH - Hayitova Shakhnoza Daniyarovna (Journals Park Publishing, 2022)
The article contains a number of recommendations for improving the methodology of organizing independent learning of students in the higher education system.
Keywords: education system; independent learning; student activity